2010
DOI: 10.1021/ja103956p
|View full text |Cite
|
Sign up to set email alerts
|

Dopant-Induced Shape Evolution of Colloidal Nanocrystals: The Case of Zinc Oxide

Abstract: The electrical, optical and other important properties of colloidal nanocrystals are determined mainly by the crystals' chemical composition, size and shape. The introduction of specific dopants is a general approach of modifying the properties of such nanocrystals in well-controlled ways. Here we show that in addition to altering the atomic composition of the nanocrystals the introduction of specific dopants can also lead to dramatic changes in morphology. The creation of Mg-doped ZnO nanocrystals provides an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
199
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 181 publications
(216 citation statements)
references
References 69 publications
15
199
1
1
Order By: Relevance
“…The similar phenomenon was also found in Mg doepd ZnO nanocrystals. 20 However, the orientation growth could not be observed in all Ni 2+ doped C-In 2 O 3 samples for their cubic structures were more difficult to grow directionally than rhombohedral structures.…”
Section: Introductionmentioning
confidence: 90%
“…The similar phenomenon was also found in Mg doepd ZnO nanocrystals. 20 However, the orientation growth could not be observed in all Ni 2+ doped C-In 2 O 3 samples for their cubic structures were more difficult to grow directionally than rhombohedral structures.…”
Section: Introductionmentioning
confidence: 90%
“…The higher reaction temperature, generally above 250℃, led to improve crystalline features of ZnO nanocrystals [11]. This approach also allows effective size control in a wide range from about 3 nm up to 15 nm [11][12][13]. In addition, a few recent studies demonstrated the syntheses of doped ZnO nanocrystals by this approach, which generated materials with tailored electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a few recent studies demonstrated the syntheses of doped ZnO nanocrystals by this approach, which generated materials with tailored electrical properties. For example, our group demonstrated the syntheses of alloyed Mg x Zn 1-x O [12] and Cd x Zn 1-x O [13] nanocrystals having tunable opti-cal bandgaps. Buonsanti et al prepared Al 3+ doped ZnO nanocrystals which had high free carrier concentrations [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper deals with the preparation of doped and non-doped nano MgO membranes using a polymeric sol-gel method that offers the possibility of controlling the synthesis of thin film hierarchical internal structure (Crisan et al 2000). Doping MgO with ZnO is studied in order to create doped nanocrystals and nanostructures with unprecedented properties (Yang et al, 2010). The effect of ZnO doping on thermal, surface and structural properties is studied.…”
Section: Introductionmentioning
confidence: 99%